2010
DOI: 10.1007/s11626-010-9346-7
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for establishment and characterization of extrahepatic bile duct epithelial cells from mice

Abstract: Culture of extrahepatic bile duct epithelial cells is a useful model to investigate physiology of extrahepatic bile duct epithelia and hepatobiliary disease mechanisms. The aim of this work was to establish and characterize a primary murine extrahepatic bile duct epithelial cell culture. Epithelial cells were isolated from extrahepatic bile ducts of BALB/c mice that were intraperitoneally injected with newborn bovine serum to induce the proliferation of extrahepatic bile ducts' epithelial cells and cultured on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
(15 reference statements)
0
10
0
Order By: Relevance
“…Ultrastructural analysis shows that extrahepatic bile ducts are lined by polarized cholangiocytes and have morphological phenotypes similar to that of intrahepatic cholangiocytes [42]. Intact tight junctions and microvilli (characteristic of intra- and extra-hepatic biliary epithelia) [27, 43] were present in EBDs and ECCs. Similar to EBDs, ECCs express CK-19, secretin, SR, SSTR 2 , CFTR and AE2 and respond to secretin and somatostatin with changes in cAMP levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrastructural analysis shows that extrahepatic bile ducts are lined by polarized cholangiocytes and have morphological phenotypes similar to that of intrahepatic cholangiocytes [42]. Intact tight junctions and microvilli (characteristic of intra- and extra-hepatic biliary epithelia) [27, 43] were present in EBDs and ECCs. Similar to EBDs, ECCs express CK-19, secretin, SR, SSTR 2 , CFTR and AE2 and respond to secretin and somatostatin with changes in cAMP levels.…”
Section: Discussionmentioning
confidence: 99%
“…Secretin-induced choleresis is associated with increased cAMP levels in extrahepatic bile duct tissue of humans and baboons [15]. While several in vitro culture models are available for evaluating the function of rodent and human intrahepatic cholangiocytes [2026], limited in vitro tools exist for evaluating the pathophysiology of the extrahepatic common bile duct [27–29]. Therefore, the aim of the study was to develop a cell line (ECCs) from normal extrahepatic bile ducts.…”
Section: Introductionmentioning
confidence: 99%
“…As described in our previous study [43], extrahepatic cholangiocytes were isolated, cultured and identified. The purified cholangiocytes were >95% pure [43].…”
Section: Methodsmentioning
confidence: 99%
“…The purified cholangiocytes were >95% pure [43]. The method of macrophage culture was described in Supplemental Protocol S1 .…”
Section: Methodsmentioning
confidence: 99%
“…Transmission electron microscopy (TEM) and fluorescence microscopy (FM) TEM was performed as previously reported [25] . For FM, the purified MM-MVs were stained using the PKH26 Red Fluorescent Cell Linker Kit (Sigma-Aldrich, St Louis, MO, USA) according to the kit's instructions, and the MM-MVs were observed by FM (Olympus, Tokyo, Japan).…”
Section: Isolation Of Mvsmentioning
confidence: 99%